Evaluation of structural performances of metakaolin based geopolymer concrete - Fatheali A. Shilar; Sharanabasava V. Ganachari; Veerabhadragouda B. Patil; Kottakkaran Sooppy Nisar (Journal of Materials Research and Technology, 2022)
Last few decades, there has been a substantial advancement of geopolymer (GP) as a Portland cement substitute. It is vital to investigate potential building uses for geopolymer concrete (GPC). Six different mixes were cast for an alkaline to binder (A/B) ratio of 0.25–0.50 with an interval of 0.05. Metakaolin-based geopolymer were cured at ambient temperature and tested for 7, 14, 28, and 90 days. Metakaolin-Marble (MM00) mix was observed to have a maximum slump. For an A/B ratio of 0.35, maximum compressive, split tensile, flexural strength and modulus of elasticity was achieved. For elevated temperature resistance, geopolymer concrete cubes were exposed to temperatures (T) of 200, 400, to 600 C. As the temperature increased, compressive strength (CS) reduced. As the increase of the alkaline to binder (A/B) ratio, the strength of geopolymer concrete increases up to a specific limit beyond the limit strength decline. An empirical formula for split tensile (STS) value prediction using compressive strength values is proposed, valid for determining split tensile strength value. The correlation between compressive strength, split tensile strength, flexural strength, and bulk density varies linearly for a quadratic polynomial.